ISPC Commentary on the Proposal for CRP3.6 - October 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the proposal for CRP 3.6: Dryland Cereals.